Angelina's silly little sister - Holabird, Katharine (Holabird, Katharine. Angelina Ballerina., 2007)
Polly always seems to get in the way when Angelina and Alice want to play alone, and so they agree to play hide-and-seek with her but then leave her in her hiding place while they play inside.